2011
DOI: 10.1038/ismej.2011.31
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and functional analysis of luxS genes in Vibrios from marine sponges Mycale laxissima and Ircinia strobilina

Abstract: Sponges harbor highly diverse and dense microbial communities, providing an environment in which bacterial signaling may be important. Quorum sensing (QS) is a cell density-dependent signaling process that bacteria employ to coordinate and regulate their gene expression. Previous studies have found that bacteria isolated from sponges are able to produce acyl-homoserine lactones (AHLs), an important class of QS molecules found in proteobacteria. Autoinducer-2 (AI-2) is a second class of QS molecule, and is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…This diversity of luxS genes in our study agree with previous studies (Gattiker et al, 2002;Zan et al, 2011) which reported that, LuxS genes are greatly divergent among Gram-positive and Gram-negative bacteria, but may have the same functions and are considered to be conserved in many bacterial species.…”
Section: Discussionsupporting
confidence: 93%
“…This diversity of luxS genes in our study agree with previous studies (Gattiker et al, 2002;Zan et al, 2011) which reported that, LuxS genes are greatly divergent among Gram-positive and Gram-negative bacteria, but may have the same functions and are considered to be conserved in many bacterial species.…”
Section: Discussionsupporting
confidence: 93%
“…Samples of M. laxissima were collected by SCUBA diving at Conch Reef, Key Largo, Florida in late October 2008 at a depth of c. 20 m as described by Zan et al . (2011a).…”
Section: Methodsmentioning
confidence: 99%
“…Samples of M. laxissima were collected by SCUBA diving at Conch Reef, Key Largo, Florida in late October 2008 at a depth of c. 20 m as described by Zan et al (2011a). Sponge samples were rinsed 3¥ with sterile artificial seawater (ASW) and were stored in RNAlater solution (Qiagen, Valencia, CA, USA) immediately for RNA extraction.…”
Section: Rna Extraction and Rt-pcr From Sponge Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…This dense microbial community associated with sponges provides conditions in which quorum sensing (QS) may be important (3,8). QS is a process by which bacteria coordinate group activities such as bioluminescence, antibiotic production, and virulence at high cell density via signal molecules, typified by N-acylhomoserine lactone (AHL) in Proteobacteria (2).…”
mentioning
confidence: 99%